2023
DOI: 10.3390/plants13010115
|View full text |Cite
|
Sign up to set email alerts
|

Magic Blue Light: A Versatile Mediator of Plant Elongation

Yun Kong,
Youbin Zheng

Abstract: Blue light plays an important role in regulating plant elongation. However, due to the limitations of older lighting technologies, the responses of plants to pure blue light have not been fully studied, and some of our understandings of the functions of blue light in the literature need to be revisited. This review consolidates and analyzes the diverse findings from previous studies on blue-light-mediated plant elongation. By synthesizing the contrasting results, we uncover the underlying mechanisms and explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 152 publications
(327 reference statements)
0
3
0
Order By: Relevance
“…Like diverse plant elongation responses to BL as presented in our recent review [3], inconsistent results have also been reported on plant flowering response to the BL manipulation through electric lighting in the literature. This would affect its application in commercial plant production.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Like diverse plant elongation responses to BL as presented in our recent review [3], inconsistent results have also been reported on plant flowering response to the BL manipulation through electric lighting in the literature. This would affect its application in commercial plant production.…”
Section: Introductionmentioning
confidence: 67%
“…In controlled environments such as a greenhouse and vertical farm, BL can be more precisely manipulated through electric lighting, especially with the development of LED technology. Unlike traditional lighting, blue LEDs can provide narrow-band BL without containing other light wavelengths (i.e., pure BL), which can affect photoreceptors' activity differently from impure BL (i.e., normally including low-levels other wavelengths) from non-LED lighting [3]. Also, blue LEDs have become more and more efficient and inexpensive for commercial applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that plants are grown under blue light, inhibiting elongation to produce short, thick, dense plants with increasing root development, whereas isolated red light creates tall, stretched plants with thin leaves and long stems [ 54 , 55 , 56 , 57 ]. This is also confirmed in this study, as hemp seedlings were under significant ( p < 0.05) influence of light treatment, whereas greater values of all morphological parameters were recorded on white light (FLUO).…”
Section: Discussionmentioning
confidence: 99%